2015
DOI: 10.1242/jcs.158121
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of the RhoA GEF Net1A controls its subcellular localization and activity

Abstract: Net1 isoform A (Net1A) is a RhoA GEF that is required for cell motility and invasion in multiple cancers. Nuclear localization of Net1A negatively regulates its activity, and we have recently shown that Rac1 stimulates Net1A relocalization to the plasma membrane to promote RhoA activation and cytoskeletal reorganization. However, mechanisms controlling the subcellular localization of Net1A are not well understood. Here, we show that Net1A contains two nuclear localization signal (NLS) sequences within its Nter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 43 publications
5
52
0
Order By: Relevance
“…Finally, the sixth group transfer metabolite, acetyl-CoA, is used to acetylate the RhoA-specific GEF partner protein, completing the full panoply of group transfers and exemplifying extensive combinatorial diversification of proteomes 163 . The extent to which any given Rho protein molecule in a cellular population has multiple modifications is not well quantitated nor is the net activity of such multiply-modified Rho species well-evaluated.…”
Section: Intersection and Convergence Of The Posttranslational Momentioning
confidence: 99%
“…Finally, the sixth group transfer metabolite, acetyl-CoA, is used to acetylate the RhoA-specific GEF partner protein, completing the full panoply of group transfers and exemplifying extensive combinatorial diversification of proteomes 163 . The extent to which any given Rho protein molecule in a cellular population has multiple modifications is not well quantitated nor is the net activity of such multiply-modified Rho species well-evaluated.…”
Section: Intersection and Convergence Of The Posttranslational Momentioning
confidence: 99%
“…MYC-nick associates with acetyltransferase and induces acetylation of several cytoplasmic proteins, among which we characterized α-tubulin and ATG3 (15,16). We speculate that MYCnick binding and acetylation of cytoplasmic factors, such as specific GAPs or GEFs, could account for modulation of Cdc42 activity by MYC-nick (45). Similarly, MYC-nick may influence cytoplasmic signaling to the nucleus, or perhaps itself serve as a transcriptional cofactor, leading to the expression of fascin or other genes.…”
Section: Discussionmentioning
confidence: 93%
“…Fascin and Cdc42 function in coordination to promote filopodia formation and to drive cell migration (43)(44)(45). Moreover, Cdc42 was shown to regulate fascin localization and function.…”
Section: Induction Of Fascin and Activation Of Cdc42 By Myc-nick Arementioning
confidence: 99%
“…Previous work has shown that acetylation can promote E3 ligase-mediated ubiquitination in multiple proteins subject to rapid turnover (Jiang et al, 2011; Liu et al, 2013b; Wang et al, 2012). In some contexts, acetylation also regulates subcellular localization to facilitate proteasomal degradation of the target protein (Fujita et al, 2015; Song et al, 2015). Future studies are needed to fully understand how acetylation is integrated into the regulatory network regulating Slug abundance and its downstream biological effects.…”
Section: Discussionmentioning
confidence: 99%